Metabolites with Anti-Inflammatory Activities Isolated from the Mangrove Endophytic Fungus Dothiorella sp. ZJQQYZ-1 - Zhaokun Li; Junhao Zhu; Ruxue Mu; Chenxi Wang; Yuru Sun; Bingbing Qian; Ning Li; Yan Chen (Microorganisms)
As special condition-derived microorganisms, mangrove endophytic fungi can produce abundant and active secondary metabolites. In this paper, one strain of Dothiorella sp. ZJQQYZ-1 was isolated from Kandelia candel. As a result, six compounds were obtained from Dothiorella sp. ZJQQYZ-1, including three new benzofuran derivatives dothiofurans A-C (1–3), one new sesquiterpene dothiopene A (4), one new steroid phomosterol C (5), and three known analogs phomosterol B (6), phomosterol A (7), and pergillin (8). Their structures were characterized by extensive spectroscopic analysis, electronic circular dichroism (ECD), and 13C NMR calculations. The bioactive assay showed that 7 exhibited significant anti-inflammatory activity with an IC50 value of 4.6 μM. Furthermore, 7 effectivity suppressed the protein expression of inducible nitric oxide synthase (iNOS) in LPS-stimulated RAW264.7 cells.